THE EFFECT OF SOCIAL MEDIA BRAND COMMUNICATION ON CONSUMER BASED EQUITY OF INDOMIE IN SURABAYA - Angel Aprilia Susilo; Silvia Margaretha; Christina Rahardja Honantha (Journal of Management and Business, 2016)
The purpose of this study is to examine the effect of Social Media Brand Communication on Consumer Based Brand Equity of Indomie in Surabaya. Data from 150 respondent in Surabaya were analyzed using Structural Equation Model (SEM) via Amos version 22. Respondent were randomly drawn from Surabaya society who joined the Fan Page of Indomie on Facebook. Result of this study showed that firm-created and user-generated social media brand communication positively influences Brand Awareness/Association, but has no influences on brand loyalty, and perceived quality only affected by user-generated social media brand communication.